THE TOYOMARTO CULTURAL TOURISM PARK Cultural Tourism Park Design Based on Heritage & Healing Retreat with Contextual Architecture Approach - Lutfan Ridharyanto; Junianto; Septi Dwi Cahyani (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
Toyomarto Village has a great potential that can be explored to encourage high and sustainable economic growth from the tourism sector. The geography is very profitable for Toyomarto Village because it is located on the foot of Mount Arjuna so that it has an exotic panorama and still maintains its beauty. In addition to abundant natural resources, Toyomarto Village also has a rich history and culture that dates back to the 14th century, when Toyomarto Village was the civilization area of the Majapahit Kingdom. The background of the naming of Toyomarto Village is derived from the Javanese language which means Toya (Water) A (No) Marta (Dead), interpreted as the water of life, this is related to the water sources that are of very high quality and abundant. Therefore, it is very feasible to design a cultural tourism park that raises the locality of Toyomarto Village using a contextual architecture approach.